Free Flap Reconstruction of Head and Neck Defects after Oncologic Ablation: One Surgeon's Outcomes in 42 Cases - Lim, Yun Sub; Kim, Jun Sik; Kim, Nam Gyun; Lee, Kyung Suk; Choi, Jae Hoon; Park, Sang Woo (Archives of Plastic Surgery, 2014)
Background Free flap surgery for head and neck defects has gained popularity as an advanced microvascular surgical technique. The aims of this study are first, to determine whether the known risk factors such as comorbidity, tobacco use, obesity, and radiation increase the complications of a free flap transfer, and second, to identify the incidence of complications in a radial forearm free flap and an anterolateral thigh perforator flap.Methods We reviewed the medical records of patients with head and neck cancer who underwent reconstruction with free flap between May 1994 and May 2012 at our department of plastic and reconstructive surgery.Results The patients included 36 men and 6 women, with a mean age of 59.38 years. The most common primary tumor site was the tongue (38%). The most commonly used free flap was the radial forearm free flap (57%), followed by the anterolateral thigh perforator free flap (22%). There was no occurrence of free flap failure. In this study, risk factors of the patients did not increase the occurrence of complications. In addition, no statistically significant differences in complications were observed between the radial forearm free flap and anterolateral thigh perforator free flap.Conclusions We could conclude that the risk factors of the patient did not increase the complications of a free flap transfer. Therefore, the risk factors of patients are no longer a negative factor for a free flap transfer.
Keywords: Free tissue flaps; Postoperative complication; Risk factors